Epizootiologic background of dissimilar distribution of human cases of Lyme borreliosis and tick-borne encephalitis in a joint endemic area - Zeman, P; Januska, J (Comparative immunology, microbiology and infectious diseases, 1999)
Lyme borreliosis (LB) and tick-borne encephalitis (TBE) are co-endemic in some parts of Europe, however, their distribution differs despite a common tick vector and comparable animal hosts. A serosurvey of game and small mammals was made in a highly endemic area and compared with historical data in human cases; the epidemiologic risk and the population density of game were modelled using a geographic information system. While LB-risk corresponded with an overall population density of game (red deer, roe deer, mouflon, wild boar) regardless of mouse abundance, TBE-risk suggested a dependence on the abundance of mice on the one hand, and game, particularly roe deer, on the other. While the prevalence of TBE-antibodies generally grew with the game's age, it was virtually constant at about 65% in LB irrespective of species. It implies a cumulation of scarce TBE-infection histories during the game's lifetime, and thus a limited size of TBE-foci relative to the living space of these animals, as well as omnipresent LB-foci, in which the animals became continuously re-infected. More ecological prerequisites seem necessary to keep TBE circulating in nature which may be responsible for its confined distribution.
Keywords: Deer; vysoká zvěř; Disease Reservoirs; Humans; nemoci zvířat; Encephalitis, Tick-Borne; Rodentia; klíšťová encefalitida; Evropa; Animal Diseases; lymeská nemoc; Lyme Disease; zdroje nemoci; věkové faktory; lidé; zvířata; Europe; myši; endemické nemoci; Mice; Swine; hlodavci; Endemic Diseases; Age Factors; Animals; prasata